Far away - Graff, Lisa (Lisa Colleen), 1981- (Puffin Books, 2019)
Summary: Twelve-year-old CJ believes her mom is dead and that she can only communicate with her through her aunt, who is a medium, but when CJ finds out that her mother is actually alive, she goes on a journey to find her.